Nilai-Nilai Pendidikan Karakter dalam Al-Qur’an (Studi Surat Al-An’am Ayat 151-153 Menurut Tafsir Al-Misbah) - Firmawati Firmawati (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2022)
This study uses qualitative research methods that are descriptive analysis, with library research data divided into primary data sources and secondary data sources obtained through collecting library materials, Selecting library materials that are used as primary data sources, Reading library materials that have been selected manually, after that an interpretive qualitative analysis was carried out. From the results of the study, it was found that the form of character education values contained in the letter Al-An’am verses 151-153 according to the interpretation of Al-Misbah, namely; a) religious, b) honest, c) responsibility, d) social care, e) polite and the values of character education contained in the letter Al-An’am verses 151-153 in the interpretation of al-Misbah can be implemented through learning in the classroom. Where the teacher is a model of the morals taught and the formation of a school environment that has good morals, then the relevance of character education in the interpretation of alMisbah to the PAI curriculum in the classroom can be seen in two sides, namely the material and the learning process. In terms of Islamic Religious Education material, the value of character education can be included. Basically, the character has the same essence and meaning as Islamic Religious Education.